Standardizing Invasive Provocation Testing for Vasospastic Angina: A Systematic Review of Diagnostic Protocols and Clinical Practice - Khair, Sufyan Mohamed; Qadeer Gill, Owais Bin; Akbar, Hina Ali; Shaikh, Roozina; Zahra Naqvi, Syeda Wafa; Mohammad Ahsan (Indus Journal of Bioscience Research, 2025)
Objective: Vasospastic angina (VSA) is an underdiagnosed condition with significant implications for patient outcomes. This systematic review evaluates the diagnostic protocols and clinical practices surrounding invasive provocation testing for VSA, with a focus on standardization and its impact on clinical outcomes. Methods: The review adhered to PRISMA guidelines and included studies from 2014 to 2024 that addressed invasive provocation testing for VSA. A total of 1,342 records were screened, with nine studies meeting the inclusion criteria. Data extraction focused on diagnostic protocols, pharmacological agents, safety measures, and clinical outcomes. Results: The findings emphasize the need for standardized diagnostic protocols for VSA, such as the COVADIS criteria, which include nitrate-responsive angina, transient ischemic ECG changes, and documented coronary artery spasm. Pharmacological agents like acetylcholine and ergonovine are commonly used, though variability in dosage, administration, and monitoring compromises standardization. Invasive provocation testing demonstrated high diagnostic utility in differentiating VSA from other forms of ANOCA, facilitating targeted interventions like calcium channel blockers. However, safety concerns and lack of clinician awareness limit its widespread adoption. Geographic disparities further exacerbate the variability in clinical practices. Conclusion: Standardization of invasive provocation testing protocols is critical for enhancing diagnostic accuracy and patient outcomes in VSA. The adoption of uniform criteria, training for healthcare professionals, and integration into clinical guidelines are essential steps toward addressing the underdiagnosis of VSA. Future research should address geographic and systemic barriers to ensure equitable implementation of standardized diagnostic practices.